2019
DOI: 10.1038/s41467-019-12254-x
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of household consumption and air pollution-related deaths in China

Abstract: Substantial quantities of air pollution and related health impacts are ultimately attributable to household consumption. However, how consumption pattern affects air pollution impacts remains unclear. Here we show, of the 1.08 (0.74–1.42) million premature deaths due to anthropogenic PM2.5 exposure in China in 2012, 20% are related to household direct emissions through fuel use and 24% are related to household indirect emissions embodied in consumption of goods and services. Income is strongly associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(69 citation statements)
references
References 62 publications
(92 reference statements)
4
64
0
Order By: Relevance
“…Whereas Vogel and Masal () noted that the vast majority of empirical public leadership studies have been conducted in the Anglo‐American context, we use a sample of 300 civil servants and their 64 supervisors from a water resource bureau and an environmental bureau in China. Public leadership and performance improvements are clearly required in this context, as recent studies estimate that more than half of the 1.4 billion Chinese citizens drink contaminated water (Yu et al ) and that there are more than a million air pollution–related premature deaths per year in China (Zhao et al ). While recent major amendments to the Chinese Water Pollution Prevention and Control Law and the Environmental Protection Law delegated more authority to environmental protection officers to discipline polluters, implementation of these laws has been poor and has not lead to the desired improvements (Hart, Zhu, and Ying ).…”
mentioning
confidence: 99%
“…Whereas Vogel and Masal () noted that the vast majority of empirical public leadership studies have been conducted in the Anglo‐American context, we use a sample of 300 civil servants and their 64 supervisors from a water resource bureau and an environmental bureau in China. Public leadership and performance improvements are clearly required in this context, as recent studies estimate that more than half of the 1.4 billion Chinese citizens drink contaminated water (Yu et al ) and that there are more than a million air pollution–related premature deaths per year in China (Zhao et al ). While recent major amendments to the Chinese Water Pollution Prevention and Control Law and the Environmental Protection Law delegated more authority to environmental protection officers to discipline polluters, implementation of these laws has been poor and has not lead to the desired improvements (Hart, Zhu, and Ying ).…”
mentioning
confidence: 99%
“…Our previous study result shown that PM 10 is the main cause of lung cancer. 2 Complexity GRA has been applied and investigated as follows:…”
Section: Grey Correlation Eory Grey Relation Analysis (Gra)mentioning
confidence: 99%
“…With a population of over 1.4 billion, China's air pollution situation is extraordinary [1]. In recent years, the annual death toll from air pollution in China is over1 million [2] and cost about China's 2.0% GDP (gross domestic product) [3].…”
Section: Introductionmentioning
confidence: 99%
“…On account of the adverse effect, outdoor air pollution carries the responsibility for the premature death of about 3 million people annually ( WHO, 2016 ) and also causes economic loss ( OECD, 2016 ). In China, assessments for the diseases burden and premature deaths from exposure to air pollution have been critically overviewed, highlighting the ability of air pollution to cause hazards for Chinese population ( GBD, 2015 Risk Factors Collaborators, 2016 ; Hu et al., 2015 ; Liu et al., 2016 ; Yang et al., 2013 ; Zhao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%